Neotripyla vulgaris gen. n., sp. n. and Semitobrilus andrassyi sp. n. (Nematoda, Triplonchida) from freshwater bodies of Vietnam - Gagarin, Vladimir G.; Gusakov, Vladimir A. (Zootaxa, 2013)
A new genus and two new species are described and illustrated from Vietnam. Neotripyla gen. n. has distinctive morphological characters of both Tripylidae and Tobrilidae. The presence of three lips, a narrow stoma with no sclerotized walls, and the arrangement of outer labial and cephalic setae are characteristic of nematodes of the family Tripylidae. The presence of vesiculate precloacal supplements in males and the absence of a muscular pouch for the spicular apparatus are characteristic of nematodes of the family Tobrilidae. Accordingly a new family, Neotripylidae fam. n., is established. Neotripyla vulgaris gen. n., sp. n. is designated the type and only species of the new genus and family. Semitobrilus andrassyi sp. n. is closely related to S. gagarini (Ebsary, 1982), but differs in the longer spicules (71–80 µm vs 65 µm long in S. gagarini) and in the presence of keel-like projection and lateral ribs at distal part of spicules. S. gagarini (Ebsary, 1982) is considered a valid species of the genus Semitobrilus. A list of all valid species of the genus Semitobrilus and key for their determination are given.